Botanchan - Ogawa, Yōko 1962- (Watashi no ehon, 2015)
Button and Buttonhole are always together on little Anna's favorite blouse, until one day Button's thread snaps. Before Mama gets out her sewing kit and reunites them, Button has an adventure rolling around Anna's room and meeting the old rattle, bib and teddy bear that helped bring Anna up as a baby